DARI FENG SHUI KE BARZANJI: Studi Transformasi Budaya Religi di Kalangan Etnis Tionghoa di Kota Donggala - Idrus A Rore; Windayanti Yanti Ati (Jurnal Pendidikan Geosfer, 2021)
This research’s aims are: 1) analyze the function of AGIL in the transformation of religious culture among ethnic Chinese in the implementation of barzanji in the city of Donggala; and 2) Analyzing the impact of religious culture transformation in the implementation of barzanji among ethnic Chinese in Donggala city. This study uses a descriptive qualitative approach. The determination of the ethnic Chinese analysis unit was carried out purposively. The research was conducted in the city of Donggala. The data collection technique used interviews, observation and documentation, while the data analysis technique used an interactive approach from Miles and Huberman consisting of; data collection, condentation, data display, and verification or drawing conclusions. The results and discussion found that: 1) From Feng Shui to barzanji as a form of religious culture transformation in the implementation of barzanji among ethnic Chinese in Donggala city, it fulfills the function of AGIL so that it is functional in social life by forming an action system consisting of: communication action system orbiting adaptation, hope action system introduces goal attainment, social action system creates integration, and cultural action system creates latency; 2) From Feng Shui to barzanji as a form of religious culture transformation in the implementation of barzanji among ethnic Chinese in the city of Donggala has implications for strengthening social solidarity. The type of social solidarity that is built is inter-ethnic spiritual solidarity in the city of Donggala. Key word:       Adaptation, goal attainment, integration, and latent pattern maintenance.